O corte etário para a etapa obrigatória da Educação Infantil: análise a partir da Psicologia Histórico-Cultural - Silva, Patricia do Nascimento da (2021)
This dissertation is linked to the research line Education, Social Policies, and State of the Stricto Sensu Graduate Program in Education/PPGE. Its study object is the National Curriculum Policies for Early Childhood Education, emphasizing the Age Cutoff. The general objective outlined is to analyze the Age Cutoff in the National Curricular Policies for the mandatory stage of Children Education from the assumptions of Cultural-Historical Psychology. As a result of the general objective, the specific objectives, which correspond to the construction of the chapters, are 1) To contextualize, from the 1990s, the Curricular Policies for Early Childhood Education, with emphasis on the emergence of the Age Cutoff for the mandatory stage; 2) To examine the conceptions of Learning and Child Development in the legislation corresponding to the Age Cutoff for the mandatory stage of Early Childhood Education from the assumptions of Cultural-Historical Psychology. The research is bibliographic and documentary, with a qualitative approach. The documentary investigation contemplates the documents that have ruled Early Childhood Education since the 1990s, specifically the National Curriculum Guidelines for Early Childhood Education of 1999, 2010, and 2017 and the respective Opinions and Resolutions that preceded them. The literature review prioritized articles, dissertations, and theses that address Curriculum Policies, Age Cutoff, and Cultural-Historical Psychology. As a result of the research, it is understood that the Age Cutoff is a mechanism implemented to guarantee that four-, five-, and six-year-old children can attend both the compulsory phase of Kindergarten and Primary School when they reach the required age until March 31st of the school year to be attended. This condition points to a confrontation with the assumptions of Cultural-Historical Psychology, especially concerning the conceptions of Learning and Child Development. Thus, the assumptions of this theory indicate the ages of three and seven years old, respectively, for entering Kindergarten and Elementary School.